2012
DOI: 10.1128/aac.01519-12
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antimicrobial Activities of Gallium Nitrate against Multidrug-Resistant Acinetobacter baumannii

Abstract: b Multidrug-resistant Acinetobacter baumannii poses a tremendous challenge to traditional antibiotic therapy. Due to the crucial role of iron in bacterial physiology and pathogenicity, we investigated iron metabolism as a possible target for anti-A. baumannii chemotherapy using gallium as an iron mimetic. Due to chemical similarity, gallium competes with iron for binding to several redox enzymes, thereby interfering with a number of essential biological reactions. We found that Ga(NO 3 ) 3 , the active compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
146
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(153 citation statements)
references
References 63 publications
6
146
1
Order By: Relevance
“…We have previously shown that Ga is protective in murine lung infection models with both Pseudomonas aeruginosa (16) and Francisella tularensis (17). Others have reported various forms of Ga to be effective in a murine P. aeruginosa burn infection model (39) and in infections caused by Rhodococcus equi (40) and Acinetobacter baumannii (5).…”
Section: Fig 5 Gallium Inhibits M Tuberculosis Aconitase Activity Amentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that Ga is protective in murine lung infection models with both Pseudomonas aeruginosa (16) and Francisella tularensis (17). Others have reported various forms of Ga to be effective in a murine P. aeruginosa burn infection model (39) and in infections caused by Rhodococcus equi (40) and Acinetobacter baumannii (5).…”
Section: Fig 5 Gallium Inhibits M Tuberculosis Aconitase Activity Amentioning
confidence: 99%
“…A series of studies by our laboratory and others demonstrated that Ga possesses antimicrobial potency against a variety of human pathogens (3,5,6,(16)(17)(18). Disruption of bacterial iron acquisition/utilization has been shown to correlate with the ability of Ga to inhibit M. tuberculosis growth as well as that of other organisms (3,5,6,16,17).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Human serum samples (2.5 ml each) were collected from 130 healthy donors following submission, comprehension, and subscription of a written informed consent. Sera were pooled, filtered, and heat inactivated (30 min at 56°C) as previously described (43). Serum chemistry was as follows: total iron, 0.78 g/ml; ferritin, 0.21 g/ml; transferrin, 2.63 mg/ml; and total iron binding capacity, 3.16 g/ml (28% transferrin saturation, equivalent to 45.6 M unsaturated iron binding sites).…”
mentioning
confidence: 99%